The Effectiveness of Using Biography Movies with and without Group Discussion in Teaching Written Recount Text (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This research focuses on improving writing ability in recount text using biography movies and group discussion. Students often fail writing tests because they associate it with spelling and punctuation. Writing is a skill which could be used to improve other skills in addition to writing in English. The teacher should be creative and innovative in order for students to easily grasp the concept of writing. The sample consisted of 36 students tenth grade from SMA Negeri 2 Pemalang. The researcher conducted experimental research. There were two groups of 18 students each: the experimental group and the control group. The research instrument was a writing test. The researcher conducted pre-test and post-test sessions. The quantitative method was used to collect data. Based on data analysis from the experimental group showed that the mean of pre-test was 68,06 while post-test was 81,78. In the control group showed that the mean of pre-test was 54,95, while post-test was 70,78. In the T-test showed that the sig. (2-tailed) of experiment and control group were 0.000
Keywords: writing ability, recount text, biography movies, group discussion